Effects of a 6-month aerobic exercise intervention on brain morphology in women with breast cancer receiving aromatase inhibitor therapy: a sub-study of the EPICC trial - Molina-Hidalgo, Cristina; Wan, Lu; Velazquez-Diaz, Daniel; Huang, Haiqing; Grove, George; Bender, Catherine M.; Gentry, Amanda L.; Sereika, Susan M.; Kang, Chaeryon; Crisafio, Mary E.; Erickson, Kirk I. (Frontiers in Human Neuroscience, 2024)
Objective: Physical exercise may increase brain volume and cortical thickness in late adulthood. However, few studies have examined the possibility for exercise to influence brain morphology in women treated for breast cancer. We conducted a nested sub-study within a randomized clinical trial to examine whether 6 months of moderate-intensity aerobic exercise in postmenopausal women with early-stage breast cancer influences brain morphology. Methods: We included twenty-eight postmenopausal women newly diagnosed with Stage 0-IIIa breast cancer (M age = 62.96 ± 5.40) who were randomized to either 45-60 minutes of supervised aerobic exercise 3 days/week (n=16) or usual care (n=12). Before beginning aromatase inhibitor aromatase inhibitor therapy, and the exercise intervention, and again at 6-month follow-up, volumetric and cortical thickness measures were derived from magnetic resonance imaging scans. Results: There were no significant intervention effects on brain volume and cortical thickness. However, greater average exercise intensity (%) during the intervention was associated with greater post-intervention cortical volume, mean cortical thickness, precentral gyrus thickness, and superior parietal thickness (all p<0.05). Finally, total supervised exercise time was associated with higher precentral gyrus thickness after the intervention (p= 0.042, R2= 0.263). Conclusions: The exercise intervention did not significantly affect brain volumes and cortical thickness compared to the control group. However, positive associations were found between exercise intensity and brain morphology changes after the 6-month intervention, indicating that exercise may reduce the vulnerability of the brain to the deleterious effects of breast cancer and its treatment.